Seawater carbonate chemistry and circadian splicing patterns in the brain of fish - Suresh, Sneha; Jarrold, Michael; Ravasi, Timothy; Munday, Philip L; Schunter, Celia (PANGAEA, 2025)
In this study, we examine the transcriptional patterns mediated by alternative splicing in driving the molecular response of fish to OA across their daily cycle. We assess the impact of environmental CO2 variation at four timepoints throughout a circadian (24-hr) day and aim to: (1) determine if the temporal patterns of splicing events in the brain in control conditions are altered by exposure to near-future predicted CO2 levels, and (2) gain a comprehensive understanding of splicing patterns under stable and fluctuating CO2 conditions by conducting pairwise comparisons between control and each CO2 condition separately for each time point. We reveal how splicing events may facilitate regulation of biological responses of fish to environmental CO2 variability across a circadian timeline. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original carbonate chemistry data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2019) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2020-02-28.
Keywords: Acanthochromis polyacanthus; Animalia; Chordata; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Gene expression (incl. proteomics); Laboratory experiment; Nekton; Pelagos; Single species; South Pacific; Tropical